Feeding practices of dairy cows in Algeria: Characterization, typology, and impact on milk production and fertility - Boukhechem, Said; Moula, Nassim; Lakhdara, Nedjoua; Kaidi, Rachid (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: To explore feeding strategies and identify eventual errors that could cause poor production and reproduction performances in dairy farms in the north of Algeria. Materials and Methods: A survey was conducted among 211 farms of different sizes, from 2014 to 2018 to compose a database that is analyzed statistically. Results: The results relative to the nutritive value of the rations showed an average dry matter intake of 15.9 ± 4.74 kg/cow/day, providing 13.2 ± 4.34 UFL (Feed Unit for Lactation) of net energy and 1306 ± 456 gm of protein digested in small intestine (PDI)/cow/day. A high proportion of concentrate intake is observed, with an average of 64.7% ± 17.4% of energy intake and 70.2% ± 16.2% of nitrogen intake. Dairy cows performances were characterized by a low milk production regarding their genetic potential (14.2 ± 4.73 kg of milk/cow/day), a calving interval > to one year (397 ± 20.4 days), though the coverage rates of their nutrient requirements reached 120%. The typology of the dietary rations allowed grouping them into three categories: deficient rations cluster (DR), correct rations cluster, and excessive rations cluster (ER). DR and ER, which are not adjusted to animals’ needs, were found in 57.8% of farms. Conclusion: It is obvious that the feeding management in the dairy farms in the North of Algeria is not based upon scientific achievements, contributing to relatively low performances of cows as well as to important financial losses. This finding imposes the necessity to adopt a correct and accurate rationing of animals. J. Adv. Vet. Anim. Res., 6(4): 567-574, December 2019